High-mobility group box 1 protein, receptor for advanced glycation end products and nucleosomes increases after marathon - Schoenfeld, Julia; Roeh, Astrid; Holdenrieder, Stefan; von Korn, Pia; Haller, Bernhard; Krueger, Kimberly; Falkai, Peter; Halle, Martin; Hasan, Alkomiet; Scherr, Johannes (Frontiers in Physiology, 2023)
Background: Prolonged and strenuous exercise has been linked to potential exercise-induced myocardial damages. One potential key to unmask the discussed underlying mechanisms of this subclinical cardiac damage could be markers of immunogenic cell damage (ICD). We investigated the kinetics of high-mobility group box 1 protein (HMGB1), soluble receptor for advanced glycation end products (sRAGE), nucleosomes, high sensitive troponin T (hs-TnT) and high sensitive C-reactive protein (hs-CRP) before and up to 12 wks post-race and described associations with routine laboratory markers and physiological covariates. Methods: In our prospective longitudinal study, 51 adults (82% males; 43±9 years) were included. All participants underwent a cardiopulmonary evaluation 10 to 12 wks pre-race. HMGB1, sRAGE, nucleosomes, hs-TnT and, hs-CRP were analysed prior, 1 to 2 wks before, immediately, 24 h, 72 h and 12 wks post-race. Results: HMGB1, sRAGE, nucleosomes and hs-TnT increased significantly from pre- to immediately post-race (0.82 to 2.79 ng/mL; 1132 to 1388 pg/mL; 9.24 to 56.65 ng/mL; 6 ng/L to 27 ng/L; p<0.001) and returned to baseline within 24 to 72 h. Hs-CRP increased significantly 24 h post-race (0.88 to 11.5 mg/L; p<0.001). Change in sRAGE was positively associated with change in hs-TnT (rs=0.352, p=0.011). Longer marathon finishing time was significantly associated with decreased levels of sRAGE (-9.2 pg/mL (β=-9.2, SE=2.2, p<0.001)). Conclusion: Prolonged and strenuous exercise increases markers of ICD immediately post-race, followed by a decrease within 72 h. An acute marathon event results in transient alterations of ICD, we assume that this is not solely driven by myocyte damages.